Larval morphology of Plagiosterna adamsii (Baly) and P. aenea (Linnaeus) with resurrection of Gastrolinoides Chûjô & Kimoto and P. formosana (Bates) (Coleoptera: Chrysomelidae: Chrysomelinae) - Cho, Hee-Wook; Świętojańska, Jolanta (Zootaxa, 2017)
Larvae of Plagiosterna adamsii (Baly, 1864) and P. aenea (Linnaeus, 1758) are redescribed and illustrated in detail, with discussion of the previous misinterpretations. The first instar larva of Plagiosterna adamsii is described for the first time. The original name and citation of P. adamsii is confirmed. The genus Gastrolinoides Chûjô & Kimoto, 1960 is resurrected from synonymy with Plagiosterna Motschulsky, 1860. Plagiosterna formosana (Bates, 1866) is resurrected from synonymy with P. aenea. A key to the larvae of the Palaearctic Plagiosterna is provided. Tubercular pattern, pigmentation and sclerotized platelets of the integument are used as diagnostic characters for particular species.